Buyer Power and Supplier Incentives - Roman Inderst; Christian Wey (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
This paper argues that - in contrast to an often expressed view - the formation of larger and more powerful buyers need not reduce welfare by stifling suppliers incentives. If contracts are determined in bilateral negotiations, the presence of larger buyers may both increase suppliersincentives for product improvement and induce suppliers to choose a more efficient technology. The paper also isolates two dierent channels by which larger buyers can obtain a discount.
Keywords: 330; Buyer power; Merger; Retailing; Nachfragemacht; Marktstruktur; Wohlfahrtseffekt; Theorie